2019
DOI: 10.1149/2.0121905jss
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pad Material Properties on CMP Performance for Sub-10nm Technologies

Abstract: It is well known that chemical mechanical polishing (CMP) pads play a dominant role in the overall performance of the polishing process. It is critical to have a fundamental understanding of the impact of the change in the pad mechanical properties on the CMP performance. The stabilization of material removal rates and planarization efficiency (PE) are demonstrated by modification of pad mechanical properties such as storage modulus. For all the pads, removal rate and PE values are compared between wafers poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The scaling-down speed of nanoscale semiconductor devices has slowed down, owing to the lithography limit as a result of large surface topography and device structure complexity 12 – 17 . In particular, the need for chemical mechanical planarization (CMP) for the removal of such surface topography has increased in nanoscale semiconductor device fabrication 18 21 . Among the CMP processes, shallow trench isolation (STI) CMP is an essential fabrication process for all nanoscale semiconductor devices, and poly-Si stop CMP is also an inevitable fabrication process for three-dimensional (3D) NAND-flash memory 22 – 26 .…”
Section: Introductionmentioning
confidence: 99%
“…The scaling-down speed of nanoscale semiconductor devices has slowed down, owing to the lithography limit as a result of large surface topography and device structure complexity 12 – 17 . In particular, the need for chemical mechanical planarization (CMP) for the removal of such surface topography has increased in nanoscale semiconductor device fabrication 18 21 . Among the CMP processes, shallow trench isolation (STI) CMP is an essential fabrication process for all nanoscale semiconductor devices, and poly-Si stop CMP is also an inevitable fabrication process for three-dimensional (3D) NAND-flash memory 22 – 26 .…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Various researchers have shown that CMP consumables such as pads, slurries, pad conditioners can significantly impact material removal rates (MRR), planarization efficiency which in turn impacts dishing performance, within-wafer non-uniformity (WIWNU), wafer-to-wafer non-uniformity (WTWNU), within-die non-uniformity (WIDNU) and defectivity of a CMP process. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] So, significant developments in the CMP consumables space will be required for the development of future technology nodes. Innovative methods and designs have been reported for the manufacturing of novel CMP pads.…”
mentioning
confidence: 99%
“…[7][8][9][10][11][12] Consumables such as CMP pads, slurries, pad conditioners, retaining rings of the carrier are known to impact material removal rates, within-wafer non-uniformity (WIWNU), wafer-to-wafer non-uniformity (WTWNU), planarization efficiency that in turn impacts the dishing performance, (WIDNU) and the defectivity of ICs. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] CMP consumable is another area that will require significant developments in addition to advances in hardware, to meet these stringent process requirements. Novel methods have been reported using advanced manufacturing technology to manufacture CMP pads.…”
mentioning
confidence: 99%